Collective All‐Carbon Magnetism in Triangulene Dimers. (18th May 2020) - Mishra, Shantanu; Beyer, Doreen; Eimre, Kristjan; Ortiz, Ricardo; Fernández‐Rossier, Joaquín; Berger, Reinhard; Gröning, Oliver; Pignedoli, Carlo A.; Fasel, Roman; Feng, Xinliang; Ruffieux, Pascal
Abstract: Triangular zigzag nanographenes, such as triangulene and its π‐extended homologues, have received widespread attention as organic nanomagnets for molecular spintronics, and may serve as building blocks for high‐spin networks with long‐range magnetic order, which are of immense fundamental and technological relevance. As a first step towards these lines, we present the on‐surface synthesis and a proof‐of‐principle experimental study of magnetism in covalently bonded triangulene dimers. On‐surface reactions of rationally designed precursor molecules on Au(111) lead to the selective formation of triangulene dimers in which the triangulene units are either directly connected through their minority sublattice atoms, or are separated via a 1, 4‐phenylene spacer. The chemical structures of the dimers have been characterized by bond‐resolved scanning tunneling microscopy. Scanning tunneling spectroscopy and inelastic electron tunneling spectroscopy measurements reveal collective singlet–triplet spin excitations in the dimers, demonstrating efficient intertriangulene magnetic coupling. Abstract : The on‐surface synthesis of covalently bonded triangulene dimers with or without a 1, 4‐phenylene spacer was achieved on Au(111). Scanning tunneling spectroscopy measurements revealed collective magnetism in the dimers in the form of singlet–triplet spin excitations, demonstrating efficient and tunable intertriangulene magnetic coupling.